T2*-weighted oxygen-enhanced pulmonary MRI in COPD is linked to resting and exertional functional measurements - Amany F Elbehairy; Jørgen Vestbo; Alex R Horsley; Geoff J M Parker; Christopher A Miller; Josephine H Naish; Hossein Baghertash (BMJ Open Respiratory Research)
Background T2*-weighted oxygen-enhanced MRI (T2*-OE-MRI) may directly assess pulmonary ventilation using oxygen as an inhaled tracer gas. It has shown promise in healthy volunteers (HVs) and cystic fibrosis but has yet to be demonstrated in patients with chronic obstructive pulmonary disease (COPD).Research question To determine the feasibility and repeatability of T2*-OE-MRI in patients with COPD. To assess correlations between T2*-OE-MRI measurements of pulmonary ventilation, pulmonary function tests (PFTs) and measures of functional limitation.Study design and methods 13 patients with mild-to-severe COPD and 13 HVs underwent PFTs, lung clearance index (LCI) measurement, incremental exercise test (patients only) and two lung MRI scans at 3 T. For T2*-OE-MRI, participants were fitted with a non-rebreathing face mask and given 100% oxygen during image acquisition.Results Patients (age: 63 (55–72) years, forced expiratory volume in 1 s (FEV1): 63 (36–79) %predicted, median (IQR)) had evidence of pulmonary gas trapping, small airway disease (SAD) and ventilation heterogeneity. During T2*-OE-MRI, the magnitude of the percentage difference between mean signal intensity at normoxia and hyperoxia (percent signal enhancement (PSE)) and the enhancing fraction (EF) were lower in patients versus HVs (2.77 (2.19–4.19) vs 5.34 (4.33–5.61) % and 0.74 (0.66–0.77) vs 0.89 (0.82–0.94), respectively, both p<0.001). Intraclass correlation coefficient values indicated moderate (0.74) and good (0.80) repeatability for PSE and EF, respectively. PSE and EF significantly correlated with FEV1, LCI and SAD indices, and in COPD, they correlated with measures of exercise capacity, dynamic hyperinflation and dyspnoea intensity during exercise.Interpretation In patients with COPD, T2*-OE-MRI is feasible and repeatable and provides regional information on pulmonary ventilation that is linked with physiological measures of disease severity, functional limitation and exertional dyspnoea.